2020
DOI: 10.1007/s40261-020-00910-w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Safety of Peficitinib (ASP015K) in Healthy Male Caucasian and Japanese Subjects

Abstract: Background and Objective Peficitinib pharmacokinetics and pharmacodynamics have been characterized mainly in Caucasian subjects. This study investigated the pharmacokinetics, pharmacodynamics, safety, and tolerability of peficitinib in healthy Japanese subjects compared with Caucasian subjects. Methods In this single-center, randomized, double-blind, placebo-controlled study, a cohort of healthy Japanese (n = 24) and Caucasian (n = 24) men received a single oral dose of peficitinib (20, 60, or 200 mg) or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…The pharmacokinetic (PK) profiles of peficitinib and its key plasma metabolites (H1, H2 and H4, shown to have very weak pharmacological activity in a cell-based assay of T-cell proliferation) 13 , 18 have been examined extensively under fasted and fed conditions (for single- and multiple-dose administration, respectively), in two phase I randomized, placebo-controlled studies in the US 19 and a phase I randomized, placebo-controlled study in Japan; with significant differences in plasma concentrations observed between subjects of different ethnicities. 16 , 17 In the latter study, C max was 45.7–98.8% higher and AUC inf was 33.8–66.4% higher in Japanese versus Caucasian subjects. 16 Additionally, peficitinib was well tolerated and dose-proportional exposure was demonstrated in each study.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The pharmacokinetic (PK) profiles of peficitinib and its key plasma metabolites (H1, H2 and H4, shown to have very weak pharmacological activity in a cell-based assay of T-cell proliferation) 13 , 18 have been examined extensively under fasted and fed conditions (for single- and multiple-dose administration, respectively), in two phase I randomized, placebo-controlled studies in the US 19 and a phase I randomized, placebo-controlled study in Japan; with significant differences in plasma concentrations observed between subjects of different ethnicities. 16 , 17 In the latter study, C max was 45.7–98.8% higher and AUC inf was 33.8–66.4% higher in Japanese versus Caucasian subjects. 16 Additionally, peficitinib was well tolerated and dose-proportional exposure was demonstrated in each study.…”
Section: Introductionmentioning
confidence: 66%
“… 12 Peficitinib has been approved for the treatment of patients with RA in Japan (2019) and Taiwan (2020). 13–15 It has also demonstrated rapid dose-proportional absorption after single- and multiple-dose administration; 16 however, absorption is delayed by a food effect following a moderate- to high-fat meal. 17 …”
Section: Introductionmentioning
confidence: 99%
“…As the RA patient model was constructed using PK data from an Asian population, the clinical relevance in other populations is currently unclear and caution should be used when applying this model to non‐Asian patients. The greater peficitinib exposure was observed in healthy Japanese compared with Caucasian with unknown reason 14 …”
Section: Discussionmentioning
confidence: 89%
“…These studies showed that peficitinib was absorbed rapidly, as demonstrated by time to maximum observed concentration (T max ) of 1.0–1.8 hours, and that food intake increased the area under the plasma concentration–time curve (AUC inf ) by 27–36% 12,13 . The mean terminal half‐life (t 1/2 ) of peficitinib ranged from 2.8 to 12.9 hours, 12 and dose‐proportional exposure was demonstrated within the dose ranges studied across single doses (3–300 mg) 12,14 . In addition, urinary excretion of peficitinib accounted for 9–15% of the oral dose, and 3 conjugated metabolites were found in plasma and urine (H2: sulfated; H4: methylated; H1: sulfated and methylated) 12,15 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation